PEMBELAJARAN MENYIMAK BERBASIS MULTIPLE INTELLIGENCES (LINGUISTIC INTELLIGENCES) - Muhafidin Muhafidin (Universitas Muhammadiyah Kuningan, 2019)
The purpose of this study was to examine the effect of Learning Models Based on Multiple Intelligences (Linguistic Intelligences) on learning outcomes listening to class VI students of SD Negeri Cidempet I and III Arahan Subdistrict, Indramayu Regency 2017-2018 Academic Year. This research is an experimental research. The population in this study were students of class I to class VI SD Negeri Cidempet I and III. The technique used in this study is Random sampling. The author randomizes it as a sample of research so that the sample obtained is a grade VI elementary school student totaling 44 students. 21 students in the experimental class and 23 students in the control class. Data collection techniques used were pretest posttest, and the results of observations. The data analysis technique in this study is the normality test and hypothesis testing (t test) used to determine the effect of Multiple Intelligences based learning models on learning outcomes listening to class VI SD Negeri Cidempet I and III Arahan Subdistrict Indramayu Regency 2017-2018 Academic Year. With a significance level of 5%, the results of the study show that the significant effect on the learning outcomes of listening skills of students who get Multiple Intelligences-based learning than students who get conventional learning